Computing Without Processors. (Communications of the ACM, 2011)
The article discusses the opportunities which heterogeneous computer hardware elements offer to computer programmers. It is noted that graphics processing units, field-programmable gate arrays, and multicore processors can be used together, each focusing on a different aspect of computer processing to which they are well suited. The Accelerator system from Microsoft is cited as an example of a data-parallel programming system which is neutral as to computer language, and can be used to drive multiple types of hardware.